A Special Report on 2019 International Planning Competition and a Comprehensive Analysis of Its Results - Chen, Jiayun; Dai, Jianrong; Nobah, Ahmad; Bai, Sen; Bi, Nan; Lai, Youqun; Li, Minghui; Tian, Yuan; Wang, Xuetao; Fu, Qi; Liang, Bin; Zhang, Tao; et al. (Frontiers in Oncology, 2020)
Purpose： The aim of this work is to introduce the 2019 International Planning Competition and to analyze its results. Methods and materials： A locally advanced non-small cell lung cancer (LA-NSCLC) case using the simultaneous integrated boost approach was selected. The plan quality was evaluated by using a ranking system in accordance with practice guidelines. Planners used their clinical TPS to generate the best possible plan along with a survey, designed to obtain medical physics aspects information. We investigated the quality of the large population of plans designed by worldwide planners using different planning and delivery systems. The correlations of plan quality with relevant planner characteristics (work experience, department scale, and competition experience) and with technological parameters (TPS and modality) were examined. Results： The number of the qualified plans was 287 with a wide range of scores (38.61–97.99). The scores showed statistically significant differences by the following factors: 1)department scale: the mean score (89.76 ± 8.36) for planners from the departments treating > 2000 patients annually was the highest of all; 2) competition experience: the mean score for the 107 planners with previous competition experience was 88.92 ± 9.59, statistically significantly from first-time participants (p = .001); 3) techniques: the mean scores for planners using VMAT (89.18 ± 6.43) and TOMO (90.62 ± 7.60) were higher than using IMRT (82.28 ± 12.47), with statistical differences (p < .001). The plan scores were negligibly correlated with the planner’s years of work experience or the type of TPS used. Regression analysis demonstrated that plan score was associated with dosimetric objectives that were difficult to achieve, which is generally consistent with a clinical practice evaluation. However, 51.2% of the planners abandoned the difficult component of total lung receiving a dose of 5 Gy in their plan design to achieve the optimal plan. Conclusion: The 2019 international planning competition was carried out successfully, and its results were analyzed. Plan quality was not correlated with work experiences or the TPS used, but it was correlated with department scale, modality, and competition experience. These findings differed from those reported in previous studies.